Mass spectrometric study of the photooxidation of the ophthalmic drugs timolol and pindolol - Criado, Susana (2003)
A mass spectrometric study of the photooxidation products of the ophthalmic drugs pindolol (1-[1H-indol-4-yloxyl]-3-[isopropylamino]-2-propanol) and timolol (S-[-]-1-[t-butylamino]-3-[(4-morpholino-1,2,5-thiadiazol-3-yl)oxyl]-2-propanol) in water has been performed by LC-MS. Based on these data and the assumption that photooxidation mainly occurs through singlet molecular oxygen attack, a possible reaction mechanism is proposed. The mechanistic pathways involve singlet oxygen attack to the pindolol indole ring and oxidation of the pindolol isopropyl or timolol terbutyl methyl groups.